EPIDEMIOLOGY OF SHAFT OF FEMUR FRACTURE IN A TERTIARY CARE HOSPITAL IN A DEVELOPING COUNTRY - Bukhari, Syed Imran; Ullah, Saleem; Noman Ali (Journal of Postgraduate Medical Institute, 2024)
Objective: To describe the epidemiology of femur shaft fracture in a developing country and develop prevention policies considering the findings. Methodology: This retrospective epidemiological study included all patients with a femur fracture who were admitted between January 2021 and April 2023 at the orthopedic and trauma surgery department of Lady Reading Hospital, Peshawar, Pakistan. The patient’s medical records were retrospectively reviewed using electronic medical records in the Hospital information system (HIS). All patients with documented femur shaft fracture who were admitted and operated on with an interlocking nail during the study period, irrespective of age, were included. Results: A total of 288 patients were identified in HMIS that had AO and were included in this study. Mean age was 31.52 ± 15.475 SD (12-91). Male to female ratio was 295:52. According to AO classification, 27 patients had 32A1 injury, 45 patients had 32A2 injury, 74 patients had 32A3 injury, 16 patients had 32B1 injury, 44 patients had 32B2 injury, 22 patients had 32B3 injury, 18 patients had 32C1 injury, 15 patients had 32C2 injury and 27 patients had 32C3 injury. Different surgical options as well as the mode of fixation were used in the management of these fractures with missing data identification in 17% of patients. Conclusion Traumatic femur fracture are not uncommon injuries in developing countries which occur due to road traffic accidents and firearm injuries in majority of the cases.